Hungry dog blues [videorecording (DVD)] - Abrams, Jason; Abrams, Jason; Hargreaves, Amy; Wilson, C.J; Gorovaia, Irina, 1989- (Freestyle Digital Media, 2023)
A small-town crime thriller set in rural Missouri, about two estranged half-brothers who kidnap the lead witness testifying against their incarcerated father to prove his innocence.